Examining the influence of foreign ownership, company website on firm performance: Evidence from Indonesia - Gustita Arnawati Putri; Doddy Setiawan (Cogent Business & Management, 2023)
Firm performance is one aspect of measuring a company's level of success. This study aims to test whether there is an influence of foreign ownership and preference of company websites on firm performance as a proxy for ROA and ROE in companies in Indonesia. The population of this study was all companies listed in the Indonesia Stock Exchange (IDX) in 2021. The sample selection used purposive sampling and obtained 264 non-financial companies as the observation data. The data were collected from the company's financial and annual reports. Multiple regression test was used to analyze this research. The results showed that the existence of foreign ownership and preference for company websites had a significant positive effect on firm performance. The finding indicates that firm performance proxied by ROA and ROE can be influenced by the company's foreign ownership structure and the preference of the company website.
Keywords: 650; company website; firm performance; foreign ownership